Hubungan Konsentrasi Belajar dan Lingkungan Belajar ketika Siswa Melaksanakan Pembelajaran Daring pada Mata Pelajaran Pemrograman Berorientasi Objek terhadap Hasil Belajar Siswa Kelas II RPL SMK Negeri 8 Malang - Wahyu Hadi Supriatmanto; Admaja Dwi Herlambang; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
In online learning situations, students study at home, so it is difficult for teachers to observe whether students are in an ideal learning environment and how students concentrate when carrying out online learning. This research is a quantitative type of causality analysis. This study seeks to find out the relation between learning concentration and learning outcomes, the relations between learning environment and learning outcomes, and also the relationship between learning concentration and learning environment together on learning outcomes. The data collection method used a questionnaire distributed and filled out by students online. The number of respondents was 51 students of class XII SMKN 8 Malang. This study uses the product moment correlation test to prove the hypothesis. The results showed (1) There was no positive and significant relation between learning concentration and learning outcomes based on a significance value of 0.600 > 0.05. (2) There is no positive and significant relations between the learning environment and learning outcomes based on a significance value of 0.962> 0.05. (3) There is no positive and significant relations between the variables of learning concentration and learning environment on learning outcomes based on a significance value of 0.764> 0.05.